Course Crediting and Academic Evaluation System of The College of Communication and Information Technology - Nero, Aries Jun M.; Fallorin, Mark A.; Antalan, , Jayza Mae R.; Sepillo, Geoffrey S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study aimed to develop a Course Crediting and Academic Evaluation System of the College of Communication and Information Technology (CCIT) in President Ramon Magsaysay State University – Iba Campus to offer an online system to ease the procedures of crediting and evaluation of the student academic records. Descriptive research design and descriptive statistics were utilized in this study. The dean, program chairpersons, and students of Bachelor of Science in Computer Science, Bachelor of Science in Computer Engineering and Bachelor of Science in Computer Engineering are the respondents of the study. The findings revealed that the respondents evaluated the software quality of the system using the International Organization for Standardization and the International Electrotechnical Commission (ISO/IEC): 25010:2011 as excellent. The respondents evaluated as strongly recommended on the degree of recommendation of the acquisition and implementation of the system. The Course Crediting and Academic Evaluation System is recommended to implement to improve the present procedures. Training to the end-users is advised to be conducted to know how to use the system. The maintenance and continuous enhancement of the system to adapt to the changing trends in information technology.